Effectiveness of New Office Technologies on Record Keeping Management at Selected Department in North Caloocan City Hall: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Technology is a fast-paced innovation, and people are adapting to it. Record-keepingmanagement plays a crucial role in any organization, and maintaining records today requiresinvesting in technology. This study aimed to determine the effectiveness of new officetechnologies on record-keeping management, the extent to which the new office technologieshelp record-keeping management and issues encountered in terms of using new officetechnologies in the record-keeping management process.The result revealed that the demographic profile of the respondents has a significant record-keeping management process in terms of using new office technology. The extent of newoffice technology had a factor in the record management process, and the respondentsresponded effectively. It emphasizes how important it is. However, the respondentsencountered issues in terms of use. Therefore, there is a need for improvement and familiarityin using new office technologies to avoid data loss and complexity.The researchers recommend that employers, institutions, and administrations should provideadequate training and schedule training sessions both during and after the introduction of thenew technology to help everyone get familiar with it.
Keywords: Business